Embarazo adolescente : características maternas y su asociación con el peso al nacer del neonato (2014)
ABSTRACT: In Colombia, adolescent pregnancy is a public health problem, with serious implications for the health and nutrition of the binomial mother-child. Objective: assess socio-demographic, economic, food security, health and maternal nutritional status characteristics by anthropometric measures in a group of pregnant adolescents in Medellin-Colombia on their third trimester of pregnancy and associate them with the newborns weight. Methods and materials: A cross sectional analytical study was made with 294 pregnant women (week 27 to 40), who participating in prenatal control program of the public hospital network in Medellin-Colombia. We sought Association of weight at birth with the explanatory variables. Results: underweight in pregnant women was presented in families that had lower income wages than the Standard Minimum Wage Income –SMWI–, adolescents who were younger than 15 years old and those who had a gynecological age less than five years. In newborns, the highest proportion of small children for pregnancy age was found in mothers who presented infections, low pregnancy weight and low family income less than the minimum wage. For those whose earnings was less than the minimum income the newborn weight decreased 118g (CI95%:-2,5 a -234,7), in addition, for each kilogram that increased the pre- pregnancy weight, newborn weight increased in 10,26g (CI95%:1,98 a -18,5). Conclusions: low-weight pregnancy and low-weight newborns are associated with low family income. Pre-pregnancy weight, body mass index in the third trimester of pregnancy and mother`s presence of urinary tract and vaginal infections were associated with the newborn ́s weight.